Comparison of Fetal Nuchal Fold Thickness Measurements by Two- and Three-Dimensional Ultrasonography (3DXI Multislice View) - Leonardo da Silva Valladão de Freitas; Fernanda Silveira de Bello Barros; Rômulo Negrini; Luiz Cláudio de Silva Bussamra; Edward Araujo Júnior; Sebastião Piato; Luciano Marcondes Machado Nardozza; Antonio Fernandes Moron; Tsutomu Aoki (Hindawi Limited, 2012)
Purpose. To compare the measurements of fetal nuchal fold (NF) thickness by two-dimensional (2D) and three-dimensional (3D) ultrasonography using the three-dimensional extended imaging (3DXI). Methods. A cross-sectional study was performed with 60 healthy pregnant women with a gestational age between 16 and 20 weeks and 6 days. The 2D-NF measurements were made as the distance from the outer skull bone to the outer skin surface in the transverse axial image in the suboccipital-bregmatic plane of the head. For the 3D we employed the 3DXI multislice view software, in which 3×2 tomographic planes was displayed on the screen and the distance between the tomographic slices was 0.5 mm. Maximum, minimum, mean, and standard deviation were calculated for 2D and 3D ultrasonography, as well the maximum and minimum, mean, and standard deviation for the difference between both methods. The Wilcoxon signed-rank test was used to compare the two different techniques. Results. 2D-NF showed a mean of thickness of 3.52±0.95 mm (1.69-7.14). The mean of 3D-NF was 3.90±1.02 mm (2.13-7.72). The mean difference between the methods was 0.38 mm, with a maximum difference of 3.12 mm. Conclusion. The NF thickness measurements obtained by 3D ultrasonography were significantly larger than those detected with 2D ultrasonography.